Rheological and mechanical behavior study of eco-friendly cement mortar made with marble powder - Kahina Chahour; Hamza Mechakra; Brahim Safi; Nacera-Melissa Dehbi; Cylia Chaibet (International Journal of Applied Mechanics and Engineering, 2024)
The work aim is to investigate the rheological and mechanical behavior of eco-friendly mortar made with marble powder. Marble have used as sand by total substitution of natural sand and as additional materials by partial substitution of cement. Firstly, rheological tests were carried out on the cement pastes in order to studying the effect of cement substitution by marble powder on the rheological behavior. Secondly, our study is devoted to evaluate the mechanical performances (flexural strength, compressive strength, mechanical behavior and ultrasonic pulse velocity) of a fluid mortar such as the case of the self-compacting mortars elaborated with the marble powder as addition materials and as a sand. The mechanical test results show that a significantly improved of compressive strength and mechanical behavior of an ecological cement mortar made with marble waste as a natural sand. However, marble-based mortars with 100% of marble sand have given a mechanical strength similar to that obtained by control cement mortar (100% natural sand). It was also noted that it can be obtained an ecological cement mortar made with 30% of marble powder as an addition supplementary materials. This leads to a reduction in cement consumption cad a reduction in CO2 gas emissions caused by cement production.